EMPATI DAN KETERAMPILAN SOSIAL - Zuchdi, Darmiyati (Jurnal Cakrawala Pendidikan, 2016)
Empathy can only be developed if we understand ourselves. Empathy makes it possible for one to be involved in a good social relationship. There are three methods to increase empathy, i.e., self introspection and the use of an intimate friend for self- reflection, asking for help from professional people, and interacting with some groups of people who are participating in emotional sensitivity training. Wholeheartedness, doing something without an eye to reward, and empathy are the main human qualities to improve social interaction. A good communication skill without these three qualities will be worth nothing. So these three aspects should be integrated in one in order to create a satisfactory relationship. There are two polarities in every person; the first one makes one have a desire to affiliate and the other makes one wish to isolate oneself. A leader of every institution, including an educational institution, should place the two. motives in proportion. Human orientation, rather than job or commodity orientation, makes it possible for a leader to see others’ perspectives as considerations in reaching a certain goal. This will lead to the development of a humanistic social interaction